Unveiling Cohesion in Senior High School Students’ Speeches: A Systemic Functional Linguistics Approach - Utama, Afrian Restu; Sri Wuli Fitriati; Zulfa Sakhiyya (SALEE: Study of Applied Linguistics and English Education, 2024)
A good speech is a speech that is easily understood by the audience. To achieve it, cohesion should be built among the clauses in the speech. This study aims to analyze the realization of theme and thematic progression in the speeches of senior high school students at the Erlangga English Speech Contest 2021. A systemic functional discourse analysis approach was employed by focusing on textual metafunction. A YouTube video entitled ‘National Grand Final Erlangga English Speech Contest 2021 Senior High School’ became the research data. The video was transcribed into written form. Four speeches were randomly chosen and labeled SHS 1, SHS 2, SHS 3, and SHS 4. The result showed that all themes were realized in the speeches. Topical and textual themes became the dominant theme. In terms of thematic development, constant theme, and multiple/ split rhyme were freely realized. This indicates that the speakers can build cohesion among the clauses. However, empty themes and failed thematic progression were still found in the speeches.